2019
DOI: 10.1097/corr.0000000000000996
|View full text |Cite
|
Sign up to set email alerts
|

What Range of Motion is Achieved 5 Years After External Rotationplasty of the Shoulder in Infants with an Obstetric Brachial Plexus Injury?

Abstract: Background Obstetric brachial plexus injuries result from traction injuries during delivery, and 30% of these children have persisting functional limitations related to an external rotation deficit of the shoulder. Little is known about the long-term effect of soft-tissue procedures of the shoulder in patients with obstetric brachial plexus injuries. Questions/purposes (1) After soft-tissue release for patients with passive external rotation less than 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Five studies in this group reported interval results in ROM, showing a mean decrease in external rotation and abduction between short-term and final follow-up. 20,31,37,40,42 The mean external rotation improvement ranged between 12° to 72° in the soft-tissue release group, 20,27,31,32,37,42 and between 29° and 128° in the soft-tissue lengthening group. 28,30,33,35,39,43 Since the surgical techniques are different, the groups cannot be compared.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Five studies in this group reported interval results in ROM, showing a mean decrease in external rotation and abduction between short-term and final follow-up. 20,31,37,40,42 The mean external rotation improvement ranged between 12° to 72° in the soft-tissue release group, 20,27,31,32,37,42 and between 29° and 128° in the soft-tissue lengthening group. 28,30,33,35,39,43 Since the surgical techniques are different, the groups cannot be compared.…”
Section: Resultsmentioning
confidence: 96%
“…After a subscapularis release with coracohumeral ligament incision, the mean active external rotation improved 33° and 35° and the mean active abduction improved by 35° and 47° at one and five years’ follow-up, respectively. 38,42 Two studies did not describe functional outcome. 34,36…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations